Sugar-Sweetened Beverage Intake and Motor Function Among Autistic and Typically Developed Children - Cao, Muqing; Gu, Tingfeng; Jin, Chengkai; Li, Xiuhong; Jing, Jin (Frontiers in Nutrition, 2022)
Background and Objectives The relationship between brain function and sugar-sweetened beverages (SSBs) is widely explored, but the motor function was not included. We aim to explore the relationship between SSBs and motor function among children with or without autism. Methods Participants were a representative autism sample (ASD, n = 106) comprising ages ranging 6–9 years and their age-matched typical counterparts (TD, n = 207), recruited in the research center of Guangzhou, China. Valid questionnaires of parent-reported including weekly SSBs intake, physical activity (PA), sedentary time (ST), and motor coordination function was used to collect relevant information. SSBs intake was further classified as no intake (no habit of taking SSBs), small to medium intake (<375 ml/week), and large intake (375 ml/week or more). Physical activity, sedentary time, and motor coordination function among the mentioned three groups as well as ASD vs. TD was compared via general linear models. Results Compared with TD children, ASD children showed less vigorous PA (4.23 ± 0.34 h vs. 2.77 ± 0.49 h, p = 0.015) as well as overall sedentary time (5.52 ± 1.89 h vs. 3.67 ± 0.28 h, 3.49 ± 0.16 h vs. 2.68 ± 0.24 h, and 34.59 ± 1.15 h vs. 23.69 ± 1.69 h, TD vs. ASD, sedentary time at weekdays, weekends and total ST in a week, respectively, all p < 0.05), lower scores in the developmental coordination disorder questionnaire (fine motor and handwriting: 14.21 ± 0.26 vs. 12.30 ± 0.38, general coordination: 28.90 ± 0.36 vs. 25.17 ± 0.53, control during movement: 24.56 ± 0.36 vs. 18.86 ± 0.53, and total score: 67.67 ± 0.75 vs. 56.33 ± 1.10, TD vs. ASD, all p < 0.05). Stratified by SSBs intake, TD children with small to medium SSBs intake showed the lowest sedentary time both on weekdays and weekends (all p < 0.05), they also performed worst in fine motor and handwriting skills (p < 0.05). Conclusion The association between SSBs and motor function was observed in typical development children, but not autistic children. A larger sample size study with a longitudinal design is warranted to confirm the association between SSBs and sedentary time among typically developed children and the potential causation direction.